Photoconductivity study of TiO2 thin films annealed in oxygen ambient / Anis Ataillah Ismail - Ismail, Anis Ataillah (2010)
The main objective of this thesis is to present the research on photoconductivity of TiO2 thin film annealed in oxygen ambient. Titanium dioxide thin films have been deposited on glass substrate by sol gel technique (dip coating method) at various oxygen flow rate. The electrical conductivity, surface morphology and optical properties of these thin films have been studied using Current Voltage (I-V) Measurement, SEM and UV-VIS-NIR Spectrophotometer, respectively. It is shown that in sol gel derived TiO2 thin films the oxygen adsorption has a great influence on photoconductivity. The photoconductivity depends on the ambient environment. A UV-VIS-NIR spectrum reveals all films exhibit high transmission (50%) in UV-NIR region. From I-V measurement result, the electrical properties were studied in dark and under illumination as a function of oxygen flow rate. Introduction of oxygen in TiO2 based coatings induces an increase of their electrical resistivity. The reduction hardness of TiO2 thin films with increase of the oxygen flow rate is discussed based on film structure that shown by SEM.